2014
DOI: 10.4236/ijmpcero.2014.31002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Commissioning of Commercial Monte Carlo Dose Algorithm for Air Cavity

Abstract: The purpose of this study was to compare the Pencil Beam (PB) with Monte Carlo (MC) calculated dosimetric results using phantoms for air cavity region. Measurements in Tough water phantom with air gaps were used to verify the calculated dose. The plane-parallel ionization chamber was moved from 2 mm to 20 mm behind air gap. Calculations were performed for various air gaps (1.0, 2.0, 3.0 and 4.0 cm) and field sizes (4.2 × 4.2, 6.0 × 6.0 and 9.8 × 9.8 cm 2 ). The lateral missing tissue measurement was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Hideharu Miura et al examined dose distribution in the presence of air cavities suggesting that dose reduction occurs right before the air cavity [2], which is in line with the present study. Results of this study indicate an increase in the maximum spot of the dose in the presence of cavity, which is in line with the results reported by Behrens.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hideharu Miura et al examined dose distribution in the presence of air cavities suggesting that dose reduction occurs right before the air cavity [2], which is in line with the present study. Results of this study indicate an increase in the maximum spot of the dose in the presence of cavity, which is in line with the results reported by Behrens.…”
Section: Discussionsupporting
confidence: 91%
“…Over the past years, the assessment of the effect of air inhomogeneities on absorbed dose has been the subject of research in many empirical studies using the Monte Carlo simulation. In fact, the Monte Carlo simulation is one of the most J Biomed Phys Eng 2019; 9 (1) www.jbpe.org Seif F. et al accurate calculation methods for radiotherapy dose [2,3]. In the studies carried out in this field, the occurrence of disorders due to the air inhomogeneities close to the intersection of air-tissue, and consequently, overdose and underdose in the surrounding areas have been reported [4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…Based on our design, the mouthpiece airway was the primary effect on dose distribution. Miura et al studied the dose distribution of photon beams in air cavities, and the results indicated that the dose was reduced before entering the air cavity [18]. Seif et al also studied the effect of the air in sinus cavities on radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…Behrens et al studied the build-up effects behind air cavities using Monte Carlo (MC) simulations and concluded that build up effects should be taken into consideration when choosing the accelerator energies with the increasing use of IMRT and radiosurgery and small fields[44]. It was also…”
mentioning
confidence: 99%